2015
DOI: 10.14692/jfi.11.2.68
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Fungal Rhizosphere and Its Role as Antagonist Agents of Fusarium oxysporum Causing Wilt Disease in Crysanthenum sp.

Abstract: ABSTRAKInfeksi virus merupakan salah satu kendala produksi kedelai. Penelitian dilakukan untuk mendeteksi infeksi virus pada beberapa pertanaman kedelai di Jawa. Sampel daun diambil secara acak sebanyak 50 tanaman dari tiap lokasi pertanaman kedelai di Bogor, Cirebon, Bantul, dan Ponorogo. Pengamatan dilakukan terhadap gejala yang ditemukan di lapangan dan insidensi penyakit ditentukan secara serologi menggunakan antibodi Cucumber mosaic virus (CMV), Soybean mosaic virus (SMV), Cowpea mild mottle virus (CPMMV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Entomopathogenic fungi have over 100 genera and 750 species with a wide host range 8 . Several soil-derived, including Penicillium, Paecilomyces, Trichoderma 12 , Aschersonia, Aspergillus sp, Beauveria bassiana, Cordyceps, Fusarium sp, Hypocrella, Metharizium sp, Ophiocordyceps, Penicilliumsp [13][14][15][16][17] . Efforts to exploit the ability of entomopathogenic fungi to parasitize their hosts can use bait insects 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Entomopathogenic fungi have over 100 genera and 750 species with a wide host range 8 . Several soil-derived, including Penicillium, Paecilomyces, Trichoderma 12 , Aschersonia, Aspergillus sp, Beauveria bassiana, Cordyceps, Fusarium sp, Hypocrella, Metharizium sp, Ophiocordyceps, Penicilliumsp [13][14][15][16][17] . Efforts to exploit the ability of entomopathogenic fungi to parasitize their hosts can use bait insects 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Virus infection on soybeans have the potential to cause yield loss and reduce the quality of seeds. Soybean mosaic virus (SMV) (Andayanie 2012), Cucumber mosaic virus strain soybean (CMV-S) and Pepper yellow leaf curl virus (PYLCV) (Rahim et al 2015) were reported recently infecting soybean plants in Java. Cowpea mild mottle virus (CPMMV) was first reported to cause systemic mottling, chlorotic blotches and leaf malformations in cowpea (Vigna unguiculata L.) in 1973 and to be widespread in the Eastern Region of Ghana, West Africa.…”
Section: Introductionmentioning
confidence: 99%
“…A population of microorganisms in the rhizosphere is usually more numerous and diverse than in the non-rhizosphere soil [15]. They can be beneficial to the plant since they suppress or harm the pathogens through the competition for nutrients [16].…”
Section: Introductionmentioning
confidence: 99%